Characterization of geological profiles developed in geoenvironments of the Cruzeiro do Sul Formation, southwestern Amazon - da Silva, Caline Pereira; Araújo, Edson Alves de; Silva, Jessé de França; Moreira, Willian Carlos de Lima; Negri, Francisco Ricardo; Oliveira, Wilber Moacir Souza (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
The diversity of soils and environments in the Amazon demands studies that improve the information with regard to their use and management. The objective of this study was to characterize the morphological, physical and chemical attributes of soils originating from the Cruzeiro do Sul Formation, in the Juruá Valley, Acre. Five geological profiles were selected and physical (granulometry) and chemical analyses (pH in H2O, K+, Ca2+, Mg2+, Al3+ and organic matter) were conducted, and samples of horizons and related layers were obtained. The soils showed intense deepening of the mantle of weathering, with predominance of orange and yellowish colors associated with 5 YR, 7.5 YR and 10 YR hues. Sandy clay-sandy texture was predominant, with higher proportions of fine sand at subsurface level. Acidity ranged from medium to high, with pH between 4.6 and 5.2. The levels of exchangeable bases were low, indicating the chemical poverty of the source material associated with sandy texture. The sandy texture also reflected in low levels of organic matter. Al3+ contents reached 12.05 cmolc.dm-3, which may generate phytotoxicity for plant development. CTC showed a positive correlation with Al3+ and exchangeable acidity. The soils originating from sediments of the Cruzeiro do Sul Formation present low natural fertility.